Flow Diversion for Reconstruction of Intradural Vertebral Artery Dissecting Aneurysms Causing Subarachnoid Hemorrhage—A Retrospective Study From Four Neurovascular Centers - Maybaum, Jens; Henkes, Hans; Aguilar-Pérez, Marta; Hellstern, Victoria; Gihr, Georg Alexander; Härtig, Wolfgang; Reisberg, André; Mucha, Dirk; Schüngel, Marie-Sophie; Brill, Richard; Quäschling, Ulf; Hoffmann, Karl-Titus; et al. (Frontiers in Neurology, 2021)
Objective: Dissecting aneurysms (DAs) of the vertebrobasilar territory manifesting with subarachnoid hemorrhage (SAH) are associated with significant morbi-mortality, especially in the case of re-hemorrhage. Sufficient reconstruction of the affected vessel is paramount, in particular, if a dominant vertebral artery (VA) is impacted. Reconstructive options include stent-assisted coiling and flow diversion (FD). The latter is technically less challenging and does not require catheterization of the fragile aneurysm. Our study aims to report a multicentric experience with FD for reconstruction of DA in acute SAH. Materials and Methods: This retrospective study investigated 31 patients (age: 30–78 years, mean 55.5 years) who had suffered from SAH due to a DA of the dominant VA. The patients were treated between 2010 and 2020 in one of the following German neurovascular centers: University Hospital Leipzig, Katharinenhospital Stuttgart, BG Hospital Bergmannstrost Halle/Saale, and Heinrich-Braun-Klinikum Zwickau. Clinical history, imaging, implanted devices, and outcomes were reviewed for the study. Results: Reconstruction with flow-diverting stents was performed in all cases. The p64 was implanted in 14 patients; one of them required an additional balloon-expandable stent to reconstruct severe stenosis in the target segment. One case demanded additional liquid embolization after procedural rupture, and in one case, p64 was combined with a PED. Further 13 patients were treated exclusively with the PED. The p48MW-HPC was used in two patients, one in combination with two additional Silk Vista Baby (SVB). Moreover, one patient was treated with a single SVB, one with a SILK+. Six patients died [Glasgow Outcome Scale (GOS) 1]. Causes of death were periprocedural re-hemorrhage, thrombotic occlusion of the main pulmonary artery, and delayed parenchymal hemorrhage. The remaining three patients died in the acute–subacute phase related to the severity of the initial hemorrhage and associated comorbidities. One patient became apallic (GOS 2), whereas two patients had severe disability (GOS 3) and four had moderate disability (GOS 4). Eighteen patients showed a complete recovery (GOS 5). Conclusion: Reconstruction of VA-DA in acute SAH with flow-diverting stents is a promising approach. However, the severity of the condition is reflected by high overall morbi-mortality, even despite technically successful endovascular treatment.